2019
DOI: 10.1371/journal.pone.0214120
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost sensor-integrated 3D-printed personalized prosthetic hands for children with amniotic band syndrome: A case study in sensing pressure distribution on an anatomical human-machine interface (AHMI) using 3D-printed conformal electrode arrays

Abstract: Interfacing anatomically conformal electronic components, such as sensors, with biology is central to the creation of next-generation wearable systems for health care and human augmentation applications. Thus, there is a need to establish computer-aided design and manufacturing methods for producing personalized anatomically conformal systems, such as wearable devices and human-machine interfaces (HMIs). Here, we show that a three-dimensional (3D) scanning and 3D printing process enabled the design and fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…Since, many willing medical providers can access the 3D printing devices but they lack on the skills to personalized the prosthetic to each patient in need, and hire specialized personnel to fulfill this task could increase the cost in great manner 1,[6][7][8]16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since, many willing medical providers can access the 3D printing devices but they lack on the skills to personalized the prosthetic to each patient in need, and hire specialized personnel to fulfill this task could increase the cost in great manner 1,[6][7][8]16 .…”
Section: Discussionmentioning
confidence: 99%
“…For this to be a viable option for amputees in developing countries, the hand must cost less than $100 total 15 . Not taking in consideration, the cost of skilled labor in producing such medical devices as prosthetics that may be adversely affect the production cost on developing economies 6,16 .…”
mentioning
confidence: 99%
“…Thus, approaches for personalizing generic digital models of prosthetic components could enable the fabrication of low-cost personalized prostheses for children with amniotic band syndrome. Yuxin Tong et al demonstrated that the combination of 3D scanning with 3D printing could enable the personalization of low-cost prosthetic hands with anatomically conformal electronic interfaces for children with amniotic band syndrome [155]. The authors observed that personalization of the prosthetic interface increased the tissue-prosthesis contact area by 408% relative to the non-personalized devices.…”
Section: Stage I Materials and Characterizationmentioning
confidence: 99%
“…That technology offers a whole new range of polymeric materials in which additive manufacturing can be carried out. Employing this technique, materials like epoxy resins [ 9 , 10 ], preceramic polymers [ 7 , 11 , 12 , 13 , 14 ], natural polymers [ 3 , 15 , 16 ], or conductive composite polymers [ 17 , 18 , 19 , 20 , 21 ] can be tailored as convenience for biomedical applications. Furthermore, it is the preferred technique for printing living cells by mixing them in hydrogels due to the high survival rate [ 22 , 23 , 24 , 25 , 26 ], in addition to the biocompatible water-rich environment that simulates the extracellular matrix (ECM) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This new additive manufacturing approach is very interesting for the elaboration of more complex tissues that require a precise control of cell deposition for their subsequent interactions and development. Being able to customize or specifically tailored each application for its final user during the fabrication process adds an added-value that cannot be provided by industrialized manufacturing processes [ 19 , 28 , 29 ]. DIW has the ability to build any desired shape or construction with any material that encompasses the shear thinning property.…”
Section: Introductionmentioning
confidence: 99%